Premiações nos Salões de Belo Horizonte: da "desmaterialização" à realidade do circuito artístico - Joana D'arc de Jesus Alves (2015)
This research lies in the emergence of contemporary art in Belo Horizonte, in the transformation of the art scene and the proposition of artistic dematerialization with trials that characterized the late 1960 extending to the 1970s. The artistic dematerialization proposals are trends derived from the historical avant-garde projects that questioned artistic categories established seeking the integration of art and life. The goal is to analyze the art scene changes of Minas Gerais, along with some competing works in salons and critical discourse held about them. Such analysis means filling a gap in the period 1969-1972 with regard to artistic transformations in the state capital scenario, highlighting the context of the realization of the Salões Nacionais de Arte de Belo Horizonte. The survey results show the realization of effervescence and later anemia of these salons. The metaphor is to clarify that while in 1969 the Hall expressed all boiling that transformations require this process was not followed, and in 1972 presented the innovations were not so intense.